2019
DOI: 10.1111/josh.12778
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐Bashing in Adolescents: Structural Relations with Heterosexual Matrix, Racism/Xenophobia and Attitudes Toward Bullying

Abstract: BACKGROUND: This study examined the combined influence of gender variables (specifically gender stereotypes, sexism, and genderism/transphobia) as well as racism/xenophobia and attitudes toward bullying roles on gender-bashing. METHODS:A trans-cultural sample of 2410 Spanish and Portuguese students participated in the study (mean age = 15.13).Structural equation modeling and multiple group analyses were used to examine the relationships among variables. RESULTS:The model revealed a good fit with the data for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…For instance, in Valido and colleagues’ longitudinal investigation of homophobic name-calling based on the same sample mentioned above [ 41 ], high between-person endorsement of traditional masculinities was one of the significant risk factors for teasing perpetration. Research from other countries, including Spain, Portugal [ 47 ], and Switzerland [ 48 ], has revealed similar connections.…”
Section: Literature Reviewmentioning
confidence: 84%
“…For instance, in Valido and colleagues’ longitudinal investigation of homophobic name-calling based on the same sample mentioned above [ 41 ], high between-person endorsement of traditional masculinities was one of the significant risk factors for teasing perpetration. Research from other countries, including Spain, Portugal [ 47 ], and Switzerland [ 48 ], has revealed similar connections.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Se identifica asociación entre el SH y una mayor probabilidad de ejercer VP, en concordancia con otro estudio en adolescentes espa ñoles 8 . Otros estudios relacionan los niveles altos de sexismo con una menor atribución de responsabilidad propia y una mayor culpabilización a la víctima 30 , una mayor probabilidad de no identificar la VP 31 y una mayor probabilidad de cometer otros tipos de violencia, siendo el SH más predictor, en concordancia con nuestros resultados 6,32 . Por ello, el sexismo podría actuar banalizando la violencia, también en el ámbito de la pareja, aumentando así la probabilidad de conducta violenta (VP) entre los perfiles más sexistas.…”
Section: Discussionunclassified
“…Several previous investigations have supported this and suggest that high acceptance of homosexuality is related to higher education, which promotes multiculturalism, cognitive sophistication, and complex reasoning among students. 38 , 40 , 41 However, one study 42 indicated that completing university education alone is insufficient; specifically, socially engaged practice is essential. 43 Medical and nursing training may provide students with more opportunities to learn about homosexual individuals as they meet and provide health care to various patients every day.…”
Section: Discussionmentioning
confidence: 99%